Effects of Biocatharantine and Colchicine on Ploidy and Morphological Traits of Orange Watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai ‘Citra Laga’) - Setiyobudi, Rizal Hermawan; Yusuf, Adib Fakhruddin; Daryono, Budi Setiadi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Massive production of watermelon is correlated with its nutritional value and attractive appearance. Intensification of plant breeding through polyploidization is of utmost importance in horticulture to improve productivity with desirable morphological traits. Colchicine is a common polyploid inducer with limitations, including effects on plant viability and high costs. Another anti-mitotic agent has been developed from Catharanthus roseus ethanolic extract, but the applicative provisions need further exploration. This research focuses on the efficacy and performance of biocatharantine and colchicine in improving ploidy levels with morphological evaluation on orange watermelon ‘Citra Laga’. Mature seeds were treated with 2% biocatharantine and 0.2% colchicine for 12 and 24 hours. Generally, major morphological traits are unchanged, with significant differences found only in the width of leaves and color characteristics. Flow cytometry is performed to assess the ploidy level of plant cells. Mixoploid plants containing 2C+4C+8C DNA are produced by colchicine, but the lowest germination rate is found to have a negative effect. Biocatharantine increases the peak intensities of tetraploid 4C DNA within mixoploid plants with minimum risk to plant viability. This research discovers the potential of biocatharantine as an anti-mitotic agent, with an evaluation of the octaploid success of orange watermelon ‘Citra Laga’ mediated by colchicine.